Threat sharing – a neighbourhood watch for security practitioners. (December 2015) - Kirk, Richard
Abstract : In the face of ever more sophisticated attacks the cyber-security industry stands a better chance of success if all those concerned work together. Effective security programmes will alert other users to new threats, regardless of whether they are allies or competitors. Security companies are not accustomed to sharing what they know, but they – and others – must do that if we are to make progress against the ever-growing threats, argues Richard Kirk of AlienVault. Imagine that you are at a cricket match and a stray ball heads straight for the face of your friend, who is sitting right next to you. You may think at first "phew, thankfully that avoided me so I am not in danger". But another thought might be, "I'd better save my friend before he gets a black eye or concussion".